Corrections to: A Survey on Successors of Leach Protocol - Sunil Kumar Singh; Prabhat Kumar; Jyoti Prakash Singh (IEEE Access, 2018)
In [1], Acknowledgements section was not published, the complete Acknowledgements is given in this Erratum.